Development of Pavement Management Model for Ranya Urban Street Network - Bakhtyar Mohammed Hamad; Abdulhakim Othman Salih (Zanco Journal of Pure and Applied Sciences, 2025)
The Paved roads are one of the most important and basic infrastructure, and there management is a significant issue for pavement organizations and engineers. Pavement Maintenance Management System (PMMS), which is a part of the Pavement Management System (PMS), consists of scheduled activity to obtain powerful management and cost-effective maintenance based on the Pavement Condition Index (PCI). The purpose of this research is to evaluate the pavement condition and provide a systematic plan for preventive maintenance, rehabilitation, and reconstruction of pavement roads to preserve it at an allowable level of serviceability. In this study, PAVER 7.1.3 and ArcGIS 10.8 were used to develop pavement management models for the Ranya urban network. A total of 17 roads with a combined length of 27.84 km and an area 478,750 m2 were selected. The road network includes three arterial roads two collector roads and twelve local roads that compose 33% and 25% and 42% of the total roads respectively. To assess the type, severity, and quantity of distresses, visual inspection is carried out. Moreover, by using PAVER 7.1.3, the collected data are inventoried and assessed for calculation of PCI, prediction deterioration model, and PCI prediction. PAVER 7.1.3 is integrated with ArcMap to develop (PMMS) for the Ranya urban street network and layout the outputs like PCI, rehabilitation, and maintenance priority. The outcomes shows that the PCI of the total study area, have Fair condition 67.16, including 24.5% have Good, 20% have Satisfactory, 31.5% have Fair, 20% have Poor, and 4% have Very Poor condition. This indicates that roads in Poor and Very Poor condition require immediate maintenance. Maintaining Fair-condition roads can slow deterioration, while priority repairs should address poor areas to prevent costly reconstruction. Roads in Good to Satisfactory condition can be preserved through preventive maintenance.